Unlocking employee agility through digital competency and empowerment - Ahmad Nadzim, Siti Zaleha; Abdul Halim, Hasliza (Universiti Teknologi Mara Selangor, 2025)
The main objective of this paper is to explore the relationship between digital competency and employee agility and the moderation effect of employee empowerment among administrators in Malaysian public universities. A quantitative methodology using PLS-SEM analysis conducted on 310 responses collected through the distribution of survey questions using Google Form. Digital competency (Information and data literacy, communication and collaboration, digital content creation, safety and problem solving) were found to have a positive significant relationship with employee agility. As a moderator, employee empowerment was found to strengthen the relationship between information and data literacy and employee agility. However, employee empowerment was not found to strengthen the relationship between communication and collaboration, digital content creation, safety and problem solving and employee agility. This research addressed the gap due to the limited study on employee agility and digital competency. Malaysian public universities leaders should leverage on digital competency in improving digital competence among administrators and focus on the targeted competence area of digital competency. The research also extending the Person-Environment Fit theory as well as creating new insights for Malaysian public universities leaders to leverage on digital competency, employee agility and employee empowerment.